2017
DOI: 10.1111/ajt.14224
|View full text |Cite
|
Sign up to set email alerts
|

Orthogonal Comparison of Molecular Signatures of Kidney Transplants With Subclinical and Clinical Acute Rejection: Equivalent Performance Is Agnostic to Both Technology and Platform

Abstract: We performed orthogonal technology comparisons of concurrent peripheral blood and biopsy tissue samples from 69 kidney transplant recipients, who underwent a comprehensive algorithm-driven clinical phenotyping. The sample cohort included patients with normal protocol biopsies and stable transplant function (TX, n=25), subclinical acute rejection (subAR, n=23), and clinical acute rejection (cAR, n=21). Comparisons between microarray and RNA sequencing (RNA-seq) signatures were performed, demonstrating a strong … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 50 publications
1
26
0
Order By: Relevance
“…14 We estimate that RNAseq needs >60 million "mappable" reads to capture the relatively low expression mRNAs that are most specific for rejection (eg, CTLA4, IFNG), increasing costs and time compared to microarrays. 14 We estimate that RNAseq needs >60 million "mappable" reads to capture the relatively low expression mRNAs that are most specific for rejection (eg, CTLA4, IFNG), increasing costs and time compared to microarrays.…”
Section: Genome-wide Discovery Of Mrnas Associated With Rejectionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 We estimate that RNAseq needs >60 million "mappable" reads to capture the relatively low expression mRNAs that are most specific for rejection (eg, CTLA4, IFNG), increasing costs and time compared to microarrays. 14 We estimate that RNAseq needs >60 million "mappable" reads to capture the relatively low expression mRNAs that are most specific for rejection (eg, CTLA4, IFNG), increasing costs and time compared to microarrays.…”
Section: Genome-wide Discovery Of Mrnas Associated With Rejectionmentioning
confidence: 99%
“…One report found that microarrays and RNAseq have the ability to develop similar signatures of rejection in kidney transplant patients, although the sample size was small and the depth of sequencing was low. 14 We estimate that RNAseq needs >60 million "mappable" reads to capture the relatively low expression mRNAs that are most specific for rejection (eg, CTLA4, IFNG), increasing costs and time compared to microarrays. RNAseq is not suited for routine diagnostics but is ideal for research and discovery as the alternative mRNA splicing and alternative promoters add intriguing levels of complexity and potential specificity that have not yet been explored.…”
Section: Genome-wide Discovery Of Mrnas Associated With Rejectionmentioning
confidence: 99%
“…However, luminex bead technologies used for the detection of antibodies in antigen, allele or epitope levels for HLA (7)(8)(9) and non-HLA systems (15), and molecular technologies to detect transcript signatures of diverse immunologic changes are broadening our choice of tests (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…4,31 Critical to these efforts will be improved noninvasive monitoring tools to enable recognition of new graft injury before it is clinically evident. 35,36 Though, given relative inefficacy of current therapeutic interventions, some might question the benefit of more intense long-term monitoring, we would counter that new therapies can emerge only with timely, proper diagnosis.…”
Section: Resultsmentioning
confidence: 99%